The Effectiveness of Citizen Journalism in Oversight of Public Services (Study at the South Sumatra Representative of the Ombudsman of the Republic of Indonesia) - Muhammad Budi; Amin Sihabudin (TABAYYUN, 2023)
This tesis is entitled "Effectiveness of Citizen Journalism in Oversight of Public Services" (Study at the Ombudsman of South Sumatra). The problems raised from this research are how the Effectiveness of Citizen Journalism in Oversight of Public Services for the Indonesian Ombudsman Representative of South Sumatra, what are the supporting and inhibiting factors for citizen journalism products for the Indonesian Ombudsman Representative of South Sumatra. This type of research is qualitative, the main or primary source is interviews with sources who are competent in their fields. Data collection techniques through observation and documentation and using the theory of Bogdan and Taylor. In this research, it is concluded that the effectiveness of citizen journalism (citizen journalism) has an important role in supporting the existence of an institution. Agencies certainly want to always maintain their existence in presenting information to the public. The effectiveness of citizen journalism (citizen journalism) has an important role in supporting the existence of an agency. In the circulation process of public service supervision, of course, there are supporting and inhibiting factors. Several supporting factors include; technological advances, easy delivery process, low cost and short time. Some of the inhibiting factors include; There is still a low level of critical and caring culture in society, the lack of use of technology, techniques.